2017
DOI: 10.1111/jav.01042
|View full text |Cite
|
Sign up to set email alerts
|

Sunrise in the city: disentangling drivers of the avian dawn chorus onset in urban greenspaces

Abstract: Urban systems are known to have a number of effects on avian richness, density, and morphological and behavioral traits. However, no study to date has simultaneously examined the wide range of urban variables in relation to the avian dawn chorus, a complex behavioral phenomenon. Previous studies investigating adjustments of the dawn chorus onset in urban settings have mainly been confined to relationships with noise and light levels. In addition to noise and light levels, in this study we included other potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 68 publications
1
11
0
Order By: Relevance
“…For neither of these studies, it is clear whether there was a shift or an extension of activity, as data were not collected for the full day. Another recent study in urban greenspaces (Lee et al, 2017) also reported an impact of both light and noise on dawn chorus timing, with a larger role for artificial light at night, but with an opposite effect from the studies above. Traffic noise appears to be correlated to advancing dawn chorus in tropical bird species as well, where artificial light has apparently less of an effect, probably due to little variation in day length at their latitude (Dorado-Correa et al, 2016;Marín-Gómez and MacGregor-Fors, 2019).…”
Section: Patterns and Processesmentioning
confidence: 78%
See 2 more Smart Citations
“…For neither of these studies, it is clear whether there was a shift or an extension of activity, as data were not collected for the full day. Another recent study in urban greenspaces (Lee et al, 2017) also reported an impact of both light and noise on dawn chorus timing, with a larger role for artificial light at night, but with an opposite effect from the studies above. Traffic noise appears to be correlated to advancing dawn chorus in tropical bird species as well, where artificial light has apparently less of an effect, probably due to little variation in day length at their latitude (Dorado-Correa et al, 2016;Marín-Gómez and MacGregor-Fors, 2019).…”
Section: Patterns and Processesmentioning
confidence: 78%
“…Traffic noise and street lightening are two of the most prominent pollutants that are put forward as causing changes in avian rhythms (Nordt and Klenke, 2013;Lee et al, 2017). American robins (Turdus migratorius), for example, initiated their dawn chorus during the night, especially in areas with elevated artificial light levels (Miller, 2006).…”
Section: Patterns and Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the prevalence of dawn-singing in birds and the numerous studies focused on that topic, its origin, evolution and causes remain unclear and seem to be context-dependent, differing among species, populations and studies (e.g., Staicer, Spector& Horn, 1996 ; Catchpole & Slater, 2008 ; Zhang, Celis-Murillo & Ward, 2016 ). This could be explained in part because researchers have indistinctly analysed or have even pooled calls and songs ( Poesel, Foerster & Kempenaers, 2001 ; Grava et al, 2013 ; Stanley et al, 2016 ; Lee, MacGregor-Fors & Yeh, 2017 ) to elucidate dawn chorus function (but see LaZerte, Otter & Slabbekoorn, 2017 ). Nonetheless, the bulk of dawn chorus studies have been focused on singing activity (e.g., Gil, Graves & Slater, 1999 ; Amrhein, Korner & Naguib, 2002 ; Liu, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…Staicer et al, 1996;Catchpole & Slater, 2008;Zhang et al, 2016). This could be explained in part because researchers have indistinctly analysed or have even pooled calls and songs (Poesel et al, 2001;Grava et al, 2013;Stanley et al, 2016;Lee et al, 2017) to elucidate dawn chorus function (but see LaZerte et al, 2017).…”
Section: Introductionmentioning
confidence: 99%